2017
DOI: 10.3390/pathogens6030042
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Adherence of Mycobacterium avium to Plumbing Surface Biofilms of Methylobacterium spp.

Abstract: Both Mycobacterium spp. and Methylobacterium spp. are opportunistic premise plumbing pathogens that are found on pipe surfaces in households. However, examination of data published in prior microbiological surveys indicates that Methylobacterium spp. and Mycobacterium spp. tend not to coexist in the same household plumbing biofilms. That evidence led us to test the hypothesis that Methylobacterium spp. in biofilms could inhibit the adherence of Mycobacterium avium. Measurements of adherence of M. avium cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…It has been suggested that mycobacteria should be less abundant in biofilm samples dominated by methylotrophs, particularly Methylobacterium spp. ( 37 , 38 ). In contrast to this expectation, we found that showerheads with higher abundances of Methylobacterium did not necessarily have lower proportional abundances of mycobacteria ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that mycobacteria should be less abundant in biofilm samples dominated by methylotrophs, particularly Methylobacterium spp. ( 37 , 38 ). In contrast to this expectation, we found that showerheads with higher abundances of Methylobacterium did not necessarily have lower proportional abundances of mycobacteria ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, the effect of the Methylobacterium extract did not compromise M. chimaera adherence. By contrast, other Methylobacterium strains have been found to exert an anti-adherent effect on Mycobacterium avium [35]. According to our results, the action of the Methylobacterium extract adhered on a surface takes place after the mycobacterial adherence.…”
Section: Discussionmentioning
confidence: 42%
“…is currently being developed [32,33]. Methylobacterium is a genus from Alphaproteobacteria isolated by Patt et al [34] that is a strictly aerobic bacterium and forms small rose colonies at its optimal growth temperature (25 • C) and usually inhabits water distribution systems [32,35]. Some strains of Methylobacterium genus have already demonstrated antibacterial effect against different microorganisms, both Gram-positive and Gram-negative bacteria [36][37][38], including mycobacteria [33], and fungi [36].…”
Section: Introductionmentioning
confidence: 99%
“…The technical means and value of increasing spatial and temporal resolution in other areas of public health, such as ensuring healthy drinking water [16] and optimal transformation of sewage [17] or compost, [18] will not be covered here.…”
Section: Heterogeneity In Biologymentioning
confidence: 99%